A inserção laboral dos refugiados como garantia ao princípio da dignidade da pessoa humana - Gallego, Cibele Gonçalves (2024)
A refugee is defined as a person who, due to persecution or a well-founded fear that persecution may occur due to their race, religion, association, political opinion, among others, finds themselves outside their country of origin, no longer having the opportunity to or no longer wishing to return to their State. However, considering the particularities of the situation in which refugees find themselves, who often leave their country abandoning everything they own, they need to have their right to life and dignity protected. Thus, work and proper insertion into the job market can be a means by which refugees find recovery of their own dignity, as a way of rebuilding their life and a new future